2020
DOI: 10.3389/fimmu.2020.01611
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin Ameliorates Atherosclerosis in Peripheral Artery Disease via the Toll-Like Receptor-4 Signaling Pathway in vitro and in vivo

Abstract: We investigated if corilagin can ameliorate or reverse atherosclerotic development via the toll-like receptor 4 (TLR4) signaling pathway in vitro and in vivo. Ana-1 cells or mouse peritoneal macrophages (MPMs) were stimulated with oxidized low-density lipoprotein followed by corilagin treatment. TLR4 expression in Ana-1 cells was upregulated by lentiviral transduction and downregulated by small interfering RNA. Peripheral blood mononuclear cells (PBMCs), plasma samples, and femoral arteries were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…JAK signaling also regulated development and maturation of cells of the innate and adaptive immune systems [ 57 , 58 ]. The binding of Toll-like receptors with specific adaptor proteins in the Toll-like receptor signaling pathway could promote inflammatory response and active immune response [ 25 , 59 , 60 ]. Herein, the expression of TLR1A was significantly up-regulated, and the expression of miR-1662 was significantly down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…JAK signaling also regulated development and maturation of cells of the innate and adaptive immune systems [ 57 , 58 ]. The binding of Toll-like receptors with specific adaptor proteins in the Toll-like receptor signaling pathway could promote inflammatory response and active immune response [ 25 , 59 , 60 ]. Herein, the expression of TLR1A was significantly up-regulated, and the expression of miR-1662 was significantly down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties of Madhugrit might be able to stave off diabetes-related complications like metabolic endotoxemia and atherosclerosis ( 27 , 28 , 58 ). These pleiotropic effects of Madhugrit can be correlated with the presence of corilagin which is known to be effective in the prevention of LPS-induced inflammation by the inhibition of TLR4 involved in the inflammatory cascade ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…43 TLR4 as pro-inflammatory mediator mediates pro-inflammatory pathways and promotes inflammatory response. 44,45 TLR4 expression is increased in human arterial atherosclerotic plaques and plays a major role in the initiation and progression of arterial atherosclerosis. 44,45 Our results also showed that an obvious elevation of MIME, NF-κB, P53, and TLR4 levels and oxidative stress could upregulate MIME/NF-κB/P53/TLR4 signaling pathway expression, suggesting that the oxidative stress and pro-inflammatory response were associated with multiple peripheral artery occlusions in elderly patients.…”
Section: Discussionmentioning
confidence: 99%